Improved FSM-based method for protocol conformance testing - XIE Lei; WEI Jiao-long; ZHU Guang-xi (Tongxin xuebao)
An improved FSM-based method was introduced to generate the conformance test sequences.This FSM-based method is a mixture version of unique input output（UIO） method and T method.The UIO method has better capability than T method,but the length of conformance test sequences of that is much longer.The simulation results have shown that the improved method has same fault coverage than UIO method,while the length of the test sequences is close to T method.